2017
DOI: 10.1097/ede.0000000000000666
|View full text |Cite
|
Sign up to set email alerts
|

Effort–Reward Imbalance at Work and Incident Coronary Heart Disease

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
171
2
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(193 citation statements)
references
References 39 publications
4
171
2
16
Order By: Relevance
“…On the other hand, another study with 1,809 male employees, belonging to a health insurance union of automobile dealerships in Japan, failed to find a significant relation of work stress to QT index or QTc interval (Maeda et al 2015), probably because of one question of whether the subject felt any stress at the workplace (yes/no), but not a multidimensional questionnaire like the JCQ. Individuals with effort-reward imbalance at work have an increased risk of coronary heart disease (Kivimäki et al 2012;Dragano et al 2017), and QTc prolongation has been reported to be associated with allcause mortality and cardiovascular events (Yap et al 2016). Therefore, such autonomic imbalance resulting from workrelated stress may represent a high-risk state leading to cardiovascular events, though the effects of work-related stress appear to differ among the industry types.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another study with 1,809 male employees, belonging to a health insurance union of automobile dealerships in Japan, failed to find a significant relation of work stress to QT index or QTc interval (Maeda et al 2015), probably because of one question of whether the subject felt any stress at the workplace (yes/no), but not a multidimensional questionnaire like the JCQ. Individuals with effort-reward imbalance at work have an increased risk of coronary heart disease (Kivimäki et al 2012;Dragano et al 2017), and QTc prolongation has been reported to be associated with allcause mortality and cardiovascular events (Yap et al 2016). Therefore, such autonomic imbalance resulting from workrelated stress may represent a high-risk state leading to cardiovascular events, though the effects of work-related stress appear to differ among the industry types.…”
Section: Discussionmentioning
confidence: 99%
“…High effort along with low monetary and confirmative rewards at work have been shown to increase the risk of, for example, cardiovascular disease (Dragano et al 2017), whereas good relationships, atmosphere, and support from work decrease the risk of ill-health in the form of, for example, stress and sleep disturbance (Luchman and González-Morales 2013; Nordin et al 2012). Individual factors are important to consider as well, since psychosocial factors arise in the interaction between organizational and personal demands and resources (Bolin 2009).…”
Section: Introductionmentioning
confidence: 99%
“…ERI is a known source of occupational stress with an estimated prevalence of 32% and has long been considered a risk factor for poor health (Siegrist 1996, 1998, 2002; van Vegchel et al 2005; de Jonge et al 2000; Godin et al 2005; Kikuchi et al 2010; Kivimaki et al 2007; Lehr et al 2009; Dragano et al 2017). These studies report strong associations between ERI and a number of health outcomes including increased morbidity, poor self-rated health, mental distress, depression, psychosomatic and physical health complaints, and incident coronary heart disease (CHD).…”
Section: Eri and The Physiological Stress Responsementioning
confidence: 99%
“…Allisey et al (2016) found that higher levels of reward (social support, recognition, and job security) in relation to efforts were associated with lower levels of absenteeism among police officers. A recent review of 11 European prospective studies reported that, during a 10-year follow-up time, individuals with ERI had 16% higher risk of developing CHD compared to those who did not experience ERI (Dragano et al 2017). …”
Section: Eri and The Physiological Stress Responsementioning
confidence: 99%